Improving Academic Motivation in Seventh Grade Students through Staff Development for Teachers - Mobley, Donald Graham ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
A practicum intervention was designed to increase the motivation of seventh graders in a small, non-urban school system in the southeastern United States. Many of these students exerted little effort to succeed in school by completing homework, studying lessons, and participating in classroom activities. A series of staff development workshops were held for the purpose of improving teachers' knowledge of motivational problems, causes of low student motivation, and methods of instruction. Practicum evaluation data indicated that the intervention was effective. Appendices provide a questionnaire used in documenting the problem, a weekly assessment log of teacher application of workshop ideas, pre- and post-teacher surveys on academic motivation, and a self-evaluation instrument for teachers to use in assessing their motivational practices. (Contains 17 references) (RH)
ERIC Note: Ed.D. Practicum, Nova University.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Faculty Development; Grade 7.; Junior High School Students; Junior High Schools; Learning Motivation; Middle Schools; Student Improvement; Student Motivation; Teacher Improvement; Workshops; Dissertations/Theses, Practicum Papers; Tests/Questionnaires.